BANDWIDTH OF QUANTUM OPTICAL COMMUNICATION SYSTEM - I. R. Gulakov; A. O. Zenevich; A. M. Timofeev (Приборы и методы измерений)
Impact of registered optical radiation intensity, overvoltage, dimensions of photosensitive surface, structure of p-n junction and avalanche photodetectors dead time operating in the photon counting mode on quantum optical system capacity has been carried out in this investigation. As a result, the quantum optical system maximum capacity of 81 kbit/s has been obtained.